Test-retest reliability of physiological parameters in elite junior distance runners following allometric scaling - Blagrove, R. C.; Howatson, G.; Hayes, P. R. (European Journal of Sport Science, 2017)
This study aimed to quantify the intra-individual reliability of a number of physiological variables in a group of national and international young distance runners. Sixteen (8 male, 8 female) participants (16.7 ± 1.4 years) performed a submaximal incremental running assessment followed by a maximal running test, on two occasions separated by no more than seven days. Maximal oxygen uptake (VO2max), speed at VO2max (km h-1), running economy and speed and heart rate (HR) at fixed blood lactate concentrations were determined. VOmax and running economy were scaled for differences in body mass using a power exponent derived from a larger cohort of young runners (n = 42). Running economy was expressed as oxygen cost and energy cost at the speed associated with lactate turnpoint (LTP) and the two speeds prior to LTP. Results of analysis of variance revealed an absence of systematic bias between trials. Reliability indices showed a high level of reproducibility across all parameters (typical error [TE] =2%; intra-class correlation coefficient >0.8; effect size <0.6). Expressing running economy as energy cost appears to provide superior reliability than using oxygen cost (TE ~1.5% vs. ~2%). Blood lactate and HR were liable to daily fluctuations of 0.14-0.22 mmol L-1 and 4-5 beats min-1 respectively. The minimum detectable change values (95% confidence) for each parameter are also reported. Exercise physiologists can be confident that measurement of important physiological determinants of distance running performance are highly reproducible in elite junior runners.